Pengaruh E-Sports Terhadap Spatial Thinking Pelajar SMA Jurusan IPS Kota Surakarta Tahun 2023 - Haqul Fikri Ramadhan; Pipit Wijayanti; Lintang Ronggowulan (GEADIDAKTIKA, 2025)
This study aims to analyse the extent to which E-Sports playing activities influence the Spatial Thinking ability of high school students majoring in Social Studies in Surakarta City. This study involved 150 respondents who were students majoring in Social Studies at several high schools in Surakarta, with the additional requirement that they were active players of E-Sports games. The study used a quantitative approach with a survey design. Sample selection was carried out by determining the number of respondents from the population who met the research criteria. Thus, a total of 150 social studies students who played E-Sports were used as the research sample. Data analysis techniques included normality tests, correlation tests, and simple linear regression analysis. The research findings showed that E-Sports playing activities had a positive and significant effect on spatial thinking ability. This relationship was influenced by spatial problem-solving abilities, spatial visualisation, cognitive development, and practical experience gained while playing E-Sports games. The t-value for variable X was 15.428 with a significance level of 0.000, which is below 0.05, so it can be concluded that the effect is significant.